THE EFFECTIVENESS OF SOCIO-SCIENTIFIC APPROACHES TO 21ST CENTURY SKILLS IN HIGH SCHOOL STUDENTS’ CHEMISTRY LEARNING: SYSTEMATIC LITERATURE REVIEW - Miterianifa Miterianifa; Naila Afrianti; Zakiyah Asri; Yetty Trisnayanti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Contemporary chemistry education aims to help students connect abstract concepts to real-world contexts. However, research indicates that many students continue to struggle to understand scientific literacy and its significance. The Socioscientific Issues (SSI) approach is implemented as a pedagogical strategy to bridge the gap between societal concerns and scientific content in educational settings. This study examines the impact of the SSI approach on high school students’ chemistry learning outcomes. A Systematic Literature Review (SLR) was conducted in accordance with PRISMA guidelines, utilising Google Scholar to identify relevant literature published between 2020 and 2025. From an initial pool of 200 publications, 14 articles were selected for in-depth analysis. The results demonstrate that the SSI approach is highly effective in enhancing students’ learning abilities. The majority of research emphasises Critical Thinking (43%). Scientific Literacy (36%), whereas Argumentation (14%) and Creative Thinking (7%) receive comparatively less attention. Green Chemistry emerges as the predominant topic, accounting for 65% of the studies. At the same time, subjects such as Acid-Base and Rate of Reaction are underrepresented. The SSI approach contributes to the development of Higher Order Thinking Skills (HOTS), motivation, and scientific understanding. To further cultivate these competencies, it is recommended that SSI be integrated into a broader range of chemistry topics, with increased emphasis on creative thinking and advanced argumentation..